COMMUNICATIVE FUNCTIONS AND THE MEANINGS OF SLOGANS IN PUBLIC SERVICE ADVERTISEMENTS - Seli, Sastika; Damayanti, Tari; Syafitri, Dewi (E-Link Journal, 2021)
This research aims at describing the communicative functions and the meaning of Slogans in Public Service Advertisements (PSA). This is a descriptive-qualitative research. The data derived from 20 PSA videos downloaded from Youtube. Then, they are collected through document analysis and analyzed with content analysis. There are only four types of meaning stated by Leech (1985) e.i 12 slogans with conceptual meanings, 7 slogans with connotative meanings, 7 slogans with affective meanings and 1 slogan with social meanings. Based on the Illocutionary acts, some communicative functions found in PSA slogans are 1) to invite society to do something, 2) to inform people, 3) to report or to state something important, 4) to express emotion, and 5) to convince people doing something in the future. Keywords: PSA slogans, communicative functions, language meaning, illocutionary act, speech act